2021
DOI: 10.1038/s43247-021-00184-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-growing season carbon emissions in a northern peatland are projected to increase under global warming

Abstract: Peatlands are important ecosystems that store approximately one third of terrestrial organic carbon. Non-growing season carbon fluxes significantly contribute to annual carbon budgets in peatlands, yet their response to climate change is poorly understood. Here, we investigate the governing environmental variables of non-growing season carbon emissions in a northern peatland. We develop a support-vector regression model using a continuous 13-year dataset of eddy covariance flux measurements from the Mer Blue B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…We found that soil freezing, and thawing combined with changes in air and soil temperature caused a high degree of variability in CO 2 fluxes in all treatments. This indicated that soil warming regulated and enhanced microbial respiration during the spring freeze-thaw (Byun et al, 2021;King et al, 2021;Rafat et al, 2021). We found that CO 2 fluxes were different among freeze-thaw phases where the dry phase had highest flux compared to the wet and waterlogged phases.…”
Section: Freeze Thaw Phases and Temperature Influence On Greenhouse G...mentioning
confidence: 71%
“…We found that soil freezing, and thawing combined with changes in air and soil temperature caused a high degree of variability in CO 2 fluxes in all treatments. This indicated that soil warming regulated and enhanced microbial respiration during the spring freeze-thaw (Byun et al, 2021;King et al, 2021;Rafat et al, 2021). We found that CO 2 fluxes were different among freeze-thaw phases where the dry phase had highest flux compared to the wet and waterlogged phases.…”
Section: Freeze Thaw Phases and Temperature Influence On Greenhouse G...mentioning
confidence: 71%
“…The snow depth and coverage influence both surface and subsurface processes. Snow cover insulates the soil and, hence, protects it against extreme temperature fluctuations during the winter, while patchy snow melt can expose Sphagnum mosses to light, hence, contributing to early spring photosynthesis [16,29]. If sufficient snow cover phenology information is not available, using an air or soil temperature threshold of 1°C may be the next best choice to flexibly delineate the NGS.…”
Section: Resultsmentioning
confidence: 99%
“…This has repercussions for net ecosystem-scale carbon fluxes considering the uncertainties in carbon offsets from growing season primary productivity [1][2][3][4]. A growing body of literature has emerged alluding to substantial increases in soil carbon dioxide (CO 2 ) and methane (CH 4 ) emissions during the NGS [5][6][7][8][9][10][11][12][13][14][15][16][17]. Despite these findings, there is a lack of consistency in how the NGS is defined, with the start and end dates of the NGS in a calendar year assigned differently among studies [18].…”
Section: Introductionmentioning
confidence: 99%
“…Rafat et al . (2021) 20 show that peatland carbon loss has a positive climate feedback loop based on 13 years of continuous eddy covariance flux measurements from Mer Blue Bog, Canada. Using a radiative forcing model and areal data from the Global Peatlands Database shows that forcing CH 4 emission due to rewetting activities does not damage climate change.…”
Section: Discussionmentioning
confidence: 99%